Vida Calma: CBT for Anxiety with a Spanish-Speaking Hispanic Adult. Issue 3 (27th May 2017) - Ramos, Katherine; Cortes, Jose; Wilson, Nancy; Kunik, Mark E.; Stanley, Melinda A.
ABSTRACT: Background : Hispanic adults aged 55 years and older are the fastest growing ethnic minority group in the United States facing significant mental health disparities. Barriers in accessing care have been attributed to low income, poor education, language barriers, and stigma. Cultural adaptations to existing evidence-based treatments have been encouraged to improve access. However, little is known about mental health treatments translated from English to Spanish targeting anxiety among this Hispanic age group. Objctive : This case study offers an example of how an established, manualized, cognitive-behavioral treatment for adults 55 years and older with generalized anxiety disorder (known as "Calmer Life") was translated to Spanish ("Vida Calma") and delivered to a monolingual, Hispanic 55-year-old woman. Results : Pre- and post-treatment measures showed improvements in symptoms of anxiety, depression, and life satisfaction. Conclusion : Findings suggest Vida Calma is a feasible treatment to use with a 55-year-old Spanish-speaking adult woman. Clinical Implications : Vida Calma, a Spanish language version of Calmer Life, was acceptable and feasible to deliver with a 55-year-old participant with GAD. Treatment outcomes demonstrate that Vida Calma improved the participant's anxiety, depression, and life satisfaction.